Effective Herbicide Options for Controlling Glyphosate-Resistant Palmer Amaranth in Roundup Ready 2 Xtend Soybean - V. Kumar; R. Liu; T. Lambert; D. E. Peterson; C. L. Minihan; P. W. Stahlman (Kansas Agricultural Experiment Station Research Reports, 2019)
Glyphosate-resistant (GR) Palmer amaranth has become a serious challenge for soybean producers in the mid-south and central United States, including Kansas. Field experiments were conducted at the Kansas State University Agricultural Research Center (KSU-ARC) near Hays, KS, and Kansas State University Ashland Bottoms (KSU-AB) research farm near Manhattan, KS, to determine the effectiveness of preemergence (PRE) and PRE followed by (fb) postemergence (POST) herbicide programs on GR Palmer amaranth control in Roundup Ready 2 Xtend soybean. The study site at Hays was infested with GR Palmer amaranth population prior to soybean planting; whereas, the Manhattan site had natural infestation of GR Palmer amaranth. Eleven treatments, including PRE alone and PREfbPOST-applied herbicides were investigated. All PRE treatments included Roundup PowerMax for control of other weed species, while POST treatments were mixtures of Roundup PowerMax and Engenia herbicides. A single PRE application of Fierce XLT and Panther PRO had ≥ 90% control of GR Palmer amaranth; whereas, control with Authority Elite and Zidua PRO did not exceed 83% at 6 weeks after POST (WAPOST). Combined over two locations, all PREfbPOST treatments had excellent control (≥ 96%) of GR Palmer amaranth at 6 WAPOST. No significant differences for soybean grain yield were observed among herbicide treatments at the Hays site; whereas, an approximate 10% increase in grain yield was observed with PREfbPOST vs. PRE alone programs at the Manhattan site. Based on these results, the two-pass programs (PREfbPOST) investigated in this research can be effectively used for season-long control of GR Palmer amaranth in Roundup Ready 2 Xtend soybean.
Keywords: dicamba-tolerant soybean; herbicide programs; glyphosate-resistant Palmer amaranth